Mapping of nighttime light trends and refugee population changes in Ukraine during the Russian–Ukrainian War - Huang, Chaoqing; Hong, Song; Niu, Xiaoxiao; Wu, Qian; Zhong, Yanmei; Yang, Huan; Zhang, Haoran (Frontiers in Environmental Science, 2023)
The nighttime lights accurately and coherently depict how humans live. This study uses nighttime light measurements to quantify changes in nighttime lighting and refugee population in Ukraine before and after the war. We combined the Theil–Sen estimator with the M-K test to explore the trends of nighttime light. In addition, we constructed a linear model using nighttime light data and a portion of the UNHCR refugee data. Our results reveal that 1 week after the start of the Russo-Ukrainian War, the nighttime light area and the average nighttime light DN value in Ukraine exhibited a steep decline of about 50 percent. Our findings showed taht refugee population changes calculated through models and nighttime light data were mostly consistent with UNHCR data. We thought that the nighttime light data might be used directly to dynamically estimate changes in the refugee movement throughout the war. Nighttime light changes has significant implications for international humanitarian assistance and post-war reconstruction.